Physical model for protection of cable lines and radioelectronic means of state and industrial objects from external electromagnetic influence in conditions of prevention of emergency situations - Володимир Ляшенко (Social Development & Security, 2019)
Grounded prerequisites for the development and creation of a physical model of protection of cable lines and radio electronic means of state and industrial objects from external electromagnetic influence in the conditions of emergency prevention.It is determined that the theoretical prerequisites for modeling include the condition of protection, which is the need to ensure complete neutralization of the electromagnetic impact energy, as the main factor in maintaining the proper technical condition of cable lines and radio electronic means. The second prerequisite for the creation of the model is the functional analogy between electricity and pneumatic (hydraulic), which is the basis for the development of protection of cable lines and RES in the direction of replacement of the most vulnerable electrical devices to pneumatic devices (hydraulic), which electrical and jet pneumatic (hydraulic) devices. They will also be linked through energy conversion.The basic scheme of physical model of protection of cable lines and radio electronic means in the conditions of emergency prevention at state and industrial objects connected with external electromagnetic influence, which unlike the existing ones, is created by replacement of separate electronic measuring systems by digital and analog streaming computations Pneumatic devices (hydro-automatic) devices and fiber-optic materials are used to create protection of communication channels.